Letter : from James Joyce, Grand Hôtel Britannique, Spa to Paul Léon, - Joyce, James, 1882-1941. (1934)
Copies of Ver Hulst's and Reece's letters, tell Macy that Matisse has Joyce's approval, awaits Forel's reply but expects to go to Luxembourg, told Gilbert his movements, encloses cheque for Léon's holidays, copies of the New York Herald should also go to R. McAlmon and Miss Monnier, her superstition.